2013
DOI: 10.1080/01431161.2013.777486
|View full text |Cite
|
Sign up to set email alerts
|

Estimating tropical forest biomass more accurately by integrating ALOS PALSAR and Landsat-7 ETM+ data

Abstract: Integration of multisensor data provides the opportunity to explore benefits emanating from different data sources. A fusion between fraction images derived from spectral mixture analysis of Landsat-7 ETM+ and phased array L-band synthetic aperture radar (PALSAR) is introduced. The aim of this fusion is to improve the estimation accuracy of above-ground biomass (AGB) in lowland mixed dipterocarp forest. Spectral mixture analysis was applied to decompose a mixture of spectral components of Landsat-7 ETM+ into v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 62 publications
4
36
0
Order By: Relevance
“…The NDVI information added to the SAR data in the third (c) test also improved the accuracy of SAR data alone, slightly more than that done by the SAR mean texture. This indicates a complementarity of the SAR and optical datatypes, as already shown by other researches [31,[33][34][35]53], and underlines the importance of forest cover information especially when considering simultaneously different vegetation communities, as in this study. When-in test (d)-both mean NDVI and mean HH SAR textures are added to the SAR backscattering statistics, only the first input is selected by the stepwise procedure, possibly due to the redundant cover information present in both HH and NDVI datasets.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The NDVI information added to the SAR data in the third (c) test also improved the accuracy of SAR data alone, slightly more than that done by the SAR mean texture. This indicates a complementarity of the SAR and optical datatypes, as already shown by other researches [31,[33][34][35]53], and underlines the importance of forest cover information especially when considering simultaneously different vegetation communities, as in this study. When-in test (d)-both mean NDVI and mean HH SAR textures are added to the SAR backscattering statistics, only the first input is selected by the stepwise procedure, possibly due to the redundant cover information present in both HH and NDVI datasets.…”
Section: Discussionsupporting
confidence: 50%
“…In this respect, Deng et al [33] found beneficial the addition of WorldView-2 to ALOS PALSAR in mountain Chinese forests; both Basuki et al [34] and Fedrigo et al [35] improved the ALOS PALSAR-based estimation by integrating Landsat 7 ETM+ data in tropical forests.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, PALSAR data and three classification algorithms were explored for mapping oil palm plantations in Cameroon, a hotspot region for oil palm plantations. To compare the performance of the three different classification methods, different training sample sizes (20,50,100,200, 300, 400, 500 pixels for each type) and parameters were used to conduct the classification experiments. The results showed that a map of oil palm plantations at 50m spatial resolution can be obtained using PALSAR data with the overall accuracies and Kappa coefficients above 88% and 0.79 respectively, for a bigger training sample size (i.e., more than 500 pixels per class).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used PALSAR data for forest monitoring and classification [17,[20][21][22][23][24][25][26][27][28][29]. PALSAR data are often combined with optical images such as Landsat and MODIS.…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of vegetation parameters (e.g., AGB, vegetation height, growing stock volume) can be improved by the fusing of SAR imagery with optical data (e.g., from Landsat) and complementary information such as altitude [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%